Cho hàm số $f^{}$$(^{}$$x^{}$$)^{}$$=^{}$$ax^{2}$$+^{}$$bx^{}$$+^{}$$c^{}$ Biết f(0)=3; f(1)=0; f(-1)=1 Tìm a,b,c

Question

Cho hàm số $f^{}$$(^{}$$x^{}$$)^{}$$=^{}$$ax^{2}$$+^{}$$bx^{}$$+^{}$$c^{}$
Biết f(0)=3; f(1)=0; f(-1)=1
Tìm a,b,c

in progress 0
Elliana 1 tháng 2021-11-12T02:26:48+00:00 2 Answers 4 views 0

Answers ( )

    0
    2021-11-12T02:28:13+00:00

    Đáp án:

    $a=-\dfrac{5}{2}$

    $b=-\dfrac{1}{2}$

    $c=3$

    Giải thích các bước giải:

    $f(x)=ax^2+bx+c $

    $+) f(0)=a.0^2+b.0+c=3$

    $⇒0+0+c=3$

    $⇒c=3$

    $+)f(1)=a.1^2+b.1+c=0$

    $⇒a+b+3=0$

    $⇒a+b=-3$

    $f(-1)=a.(-1)^2+b.(-1)+c=1$

    $⇒a-b+3=1$

    $⇒a-b=-2$

    $⇒a=b-2$

    Thay $a=b-2$ vào $a+b=-3$, ta được:

    $b-2+b=-3$

    $⇒2b=-1$

    $⇒b=-\dfrac{1}{2}$

    Thay $b=-\dfrac{1}{2}$ vào $a+b=-3$, ta được:

    $a-\dfrac{1}{2}=-3$

    $⇒a=-\dfrac{5}{2}$

    Vậy $a=-\dfrac{5}{2}$

           $\text{$b=-\dfrac{1}{2}$}$

           $\text{$c=3$}$

    0
    2021-11-12T02:28:18+00:00

    Đáp án:

     

    Giải thích các bước giải:

     f(x) = ax² + bx + c

    f(0) = a.0² + b.0 + c = 0+0+c = 3

    => c = 3

    f(1) = a.1² + b.1 + c = 0

    => a + b + 3 = 0

    => a + b = -3 (1)

    f(-1) = a. (-1)² + b.(-1) + c = 1

    => a – b + 3 = 1

    => a – b = -2

    =>       a = -2 + b

    Thay a = -2 + b vào (1) ta được:

      -2 + b + b = -3b -2 + b = -3

       =>      2b  = -1

      =>      b     = $\frac{1}{2}$ 

    Vậy b = $\frac{1}{2}$ 

    Thay b = $\frac{1}{2}$ b = $\frac{1}{2}$  vào (1) ta được:

       a – $\frac{1}{2}$  = -3

    =>   a    = -3 + $\frac{1}{2}$ 

             a   = $\frac{5}{2}$ 

    Vậy a = $\frac{5}{2}$ 

            b = $\frac{1}{2}$ 

            c  = 3        

    CHÚC HỌC TỐT !!!

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )